New medieval literatures, 16 - Ashe, Laura ca. 20./21. Jh; Lawton, David 1948-; Scase, Wendy 1955- (D.S. Brewer, 2016)
New Medieval Literatures - now published by Boydell and Brewer - is an annual of work on medieval textual cultures, aiming to engage with intellectual and cultural pluralism in the Middle Agesand now. Its scope is inclusive of work across the theoretical, archival, philological, and historicist methodologies associated with medieval literary studies, and embraces both the British Isles and Europe. Topics in this volume include the political ecology of Havelok the Dane: Thomas Hoccleve and the making of "Chaucer"; and Britain and the Welsh Marches in Fouke le Fitz Waryn. Contributors: Alexis Kellner Becker, Emily Dolmans, Marcel Elias, Philip Knox, Sebastian Langdell, Jonathan Morton, Marco Nievergelt, George Younge
Title from publisher's bibliographic system (viewed on 04 Jul 2016)
Keywords: Literature, Medieval / History and criticism